The films of Konrad Wolf : archive of the revolution - Powell, Larson, 1960- (Screen cultures., 2020)
"This is the first book in any language on the films of Konrad Wolf (1925-1982), East Germany's greatest filmmaker, and puts Wolf in a larger European filmic and historical context"--